The Influence of Poster Media on Flood Disaster Emergency Response Knowledge in Adolescents - Tria Nopi Herdiani; Suhita Tri Oklaini; Septa Putri Utami (Jurnal Ilmiah Multidisiplin Keilmuan Mandira Cendikia, 2025)
Floods can damage and destroy homes and farms, displace families, pets and livestock, damage crops, and disrupt agriculture and businesses. This study aims to study the Influence of Poster Media on Emergency Response Knowledge in Facing Flood Disasters among Adolescents at SMPN 11 Bengkulu City. This type of research uses pre-experimental using the One Group Pretest-Posttest design. The population of this study was all students of SMPN 11 Bengkulu City in the 2023/2024 academic year totaling 536 respondents. The sample in this study84 studentsusing Cluster Random Sampling technique. Data collection technique with primary data. Data analysis with univariate analysis, normality testusing kolmogorov smirnov techniqueand bivariateusing the Wilcoxon signed rank test. The results of the study were obtained from 84 respondents before being given poster media material, 2 respondents had Good Knowledge with a percentage (2%), sufficient knowledge 29 respondents with a percentage (35%) and insufficient knowledge 53 respondents with a percentage (63%). From 84 respondents after being given poster media material, 79 respondents had Good Knowledge with a percentage (94%), sufficient knowledge 5 respondents with a percentage (6%) and no respondents with insufficient knowledge. There is an influence of poster media on adolescent knowledge with emergency response in dealing with flood disasters at SMPN 11 Bengkulu City with a ρ value <0.05 or 0.000.